COSA Minutes & Agenda, April 2020 - Council on Staff Affairs, Valdosta State University (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 2020)
Council On Staff Affairs (COSA) meeting Minutes and agenda. April 2020.
Council On Staff Affairs (COSA) Meeting Agenda, April 23, 2020. Valdosta State University. 1 electronic document, 1 pages. Council On Staff Affairs (COSA) Minutes of Thursday, April 23, 2020. Valdosta State University. 1 electronic document, 4 pages.
Keywords: Council on Staff Affairs (Valdosta State University); Committees; Minutes (Records); Valdosta State University